Reliability and Quality of Complex Systems - A.V. Masloboev; V.N. Tsygichko (Надежность и качество сложных систем)
Background. The ongoing study is aimed at developing methods and information technologies for monitoring and assessing the resilience of critical entities and infrastructures to improve the efficiency of situational management of these complex dynamic systems. The urgency of this study is due to the need to design and integrate adaptive control systems to maintain the safety and stability of critical infrastructures under destructive impact of negative factors on their constituent elements, and the increased need for methodological, information and analytical support of the current control tasks at all phases of the resilience management life-cycle of critical entities. Materials and methods. The theoretical foundations of the study are the general theory of risk and fundamentals of safety analysis, the stateof- the-art resilience concept and the recent methodology of organizational systems management. The methodological approach to solving the problem of enhancing the stability of critical infrastructures is based on the conjugation of security risk-driven auditing and adaptive resilience management methods. Results and conclusions. The expansion of the range of application of the methodological apparatus for an integrated assessment of the security violation risk factors of critical entities, designed at the Institute of Systems Analysis of the Russian Academy of Sciences, in terms of its adaptation to critical infrastructure resilience management, has been proposed. An adapted approach based on a multilevel analysis of the potential threats model, vulnerabilities and the performance of countermeasures provides an aggregated assessment of the resilience level and a reasonable choice of recovery and adaptation profiles for maintaining and protecting the critical system functions for a given type of actuating threats. In practice, such a risk-driven approach can be used for information and analytical support of the critical infrastructure operators’ activities as a tool for preventive analytics and situational control of the critical entities resilience.